ADAB MENCARI ILMU MENURUT IMAM AL-GHAZALI DAN RELEVANSINYA DALAM MEMBENTUK AKHLAK SISWA DI ERA DIGITAL - Arrohma; Aisyah Nayla Faza; Naili Zakiyah; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The rapid development of digital technology has significantly transformed learning processes, while simultaneously creating moral challenges such as declining communication ethics, reduced respect for teachers, cyberbullying, and the spread of unverified information. This study aims to analyze Imam Al-Ghazali’s concept of etiquette in seeking knowledge and its relevance to the formation of students’ character in the digital era. This research employs a qualitative library research method. Data were collected from relevant literature, including Al-Ghazali’s works, scholarly journals, and previous studies, and were analyzed using content analysis techniques. The findings reveal that Al-Ghazali’s concept of learning etiquette is founded upon five main pillars: sincerity of intention, purification of the heart, respect for teachers, diligence in learning, and the application of knowledge in daily life. These values are highly relevant to addressing moral challenges in the digital age, as they contribute to the development of students who are disciplined, responsible, ethical, and wise in utilizing technology. Therefore, integrating Al-Ghazali’s educational values into contemporary digital learning can serve as a strategic foundation for nurturing knowledgeable individuals with strong moral character who are capable of navigating modern technological developments wisely and responsibly.